Daylight strategies simulation for educational studio facilities: Velux simulator / Muhammad Anas Othman ... [et al.] - Othman, Muhammad Anas; Jaafar, Adnin Syaza; Haron, Siti Norsazlina; Ahmad, Nur Azfahani (2021)
Malaysian universities face numerous environmental issues in the field of Educational Design Studio (EDS). The occurrence of these issues is due to varied activities and length of occupancy. Owing to unregulated use of artificial lighting, this will cause a raise in the electricity bill, resulting in more energy waste. Daylight Strategy is a method used to increase natural light penetration in EDS. Thus, this paper aims to revitalize daylight strategies in EDS by using the Velux Daylight Visualizer Software. The Interior Design Studio is chosen as the case study. This study was carried out in two phases. Phase one was a field study that took the measurement of the site and transformed it into a generic model. Phase two was model simulation through the use of Velux Daylight Visualizer Software. The Velux Daylight Visualizer Software was used to demonstrate the state of natural lighting in the generic model with respect to the degree of illuminance and daylight factor. This study found that four daylight strategies were essentially used in universities. They were placed at windows, louvres, light-shelf, and overhangs. Based on the simulation analysis, light-shelf achieved the best reading for daylight factor and illuminance, as well as meeting the typical educational lighting level standard. Integrating daylight strategies into the EDS has allowed the studio to have a higher amount of illuminance as well as brightening the studio with daylight strategies being implemented.